Energy Consumption, Emission, Transportation Sector in Malaysia: Review on Malaysia’s Road Transport - Yaacob, Fatin Farazh; Badyalina, Basri; Mohd Shariff, Sazlin Suhalmie; Ramli, Mohamad Faizal; Alpandi, Rabiatul Munirah (Information Management and Business Review, 2024)
Transportation is a major challenge for energy conservation, with road transport in Malaysia being a significant contributor to greenhouse gas (GHG) emissions. In Malaysia, traditional fossil fuels such as gasoline and diesel dominate the transportation sector, which has become the second-largest source of GHG emissions, accounting for 20% in 2014. This increase in CO2 emissions, driven by rising vehicle ownership and economic growth, underscores the urgent need for effective emission reduction strategies. The rapid growth in road transportation in Malaysia is linked to socioeconomic factors, including rising incomes and urbanization, leading to higher energy consumption and pollution. Data indicates a significant increase in vehicle registrations from 1990 to 2018, with motorcars and motorcycles being the most common. This growth, fueled by subsidies and decentralization, has exacerbated the sector’s environmental impact. The Green Technology Master Plan Malaysia 2017–2040 aims to address these issues by setting ambitious targets to enhance renewable energy, improve energy efficiency, and promote eco-friendly fuels. Key strategies include expanding public transportation, increasing the adoption of electric vehicles (EVs), and introducing alternative fuels like hydrogen. Malaysia has substantial potential to reduce CO2 emissions through initiatives such as expanding EV infrastructure, promoting natural gas vehicles, and improving public transit. Effective implementation of these strategies can significantly lower the transportation sector’s carbon footprint, contributing to a more sustainable future.